2003
DOI: 10.2174/1568026033452555
|View full text |Cite
|
Sign up to set email alerts
|

Dual Topoisomerase I / II Inhibitors in Cancer Therapy

Abstract: While the majority of topoisomerase (topo) inhibitors show selectivity against either topo I or topo II, a small class of compounds can act against both enzymes. These can be divided into three classes. The first and largest class comprise drugs that bind to DNA by intercalation and include the clinically-evaluated acridine DACA, the benzopyridoindole intoplicine, the indenoquinolinone TAS-103, the benzophenazine XR11576, and the pyrazoloacridine NSC 366140. The second category comprises hybrid molecules, prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 81 publications
0
94
0
Order By: Relevance
“…Their pharmacological properties have been previously evaluated and they have been widely used in the clinic mainly against malaria and some bacterial infections. [22][23][24][25] The anticancer activity of acridine derivatives has also been intensively evaluated. [22][23][24][25] However, the anticancer mechanism of acridine derivatives remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Their pharmacological properties have been previously evaluated and they have been widely used in the clinic mainly against malaria and some bacterial infections. [22][23][24][25] The anticancer activity of acridine derivatives has also been intensively evaluated. [22][23][24][25] However, the anticancer mechanism of acridine derivatives remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a dual topoisomerase inhibitor, BN80927 should be compared with other recently reported dual inhibitors of topoisomerase (32) having a dual poisoning mechanism of action, such as Tas-103 (33) or with a catalytic inhibition mode on either Topo I [lucanthone (34)] or both Topo I and II [such as F11782 epipodophyllotoxin derivative (35,36)]. To date, to our knowledge, BN80927 seems to be the only dual inhibitor having both Topo I poisoning and Topo II catalytic inhibitory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Because Bax(-/-) cells are resistant to acridine derivatives and CP-31398, the mitochondrial pathway must have a role in the mechanism of cell death induced by these compounds. It has also been suggested that acridine derivatives act by intercalating in DNA and subsequently inhibiting topoisomerase I or II, but like CP-31398, these compounds do not act as classic DNA-damaging agents as evidenced by lack of ser15 phosphorylation on p53 (42).…”
Section: Small Molecules Restore Wild-type P53 Activity To Cells Harbmentioning
confidence: 99%